Consumption and Food Security of Targetted Households of Empowerment Family Programe in Cikaroya and Ciwalen Village, Warung Kondang Sub-District, Cianjur, West Java - Thomas Pahlevi Harefa; Clara M Kusharto; . Retnaningsih (Media Gizi dan Keluarga, 2001)
This research aimed to identify consumption and food security at household level before and after intervention to empower family in Cikaroya and Ciwalen Village, Sub-district Warung Kondang, Cianjur West Java from July until December 2000. ¡§Experimental Before-After Design¡¨ was used in this study. Respondents covered 32 households which consist of poor families (Pra KS family and KS family). The result of this research showed that the average of household size is 6 and the average of household head age is 37,4 years old and housewife is 30,2 years old, with educational achievement, 81,3% household heads and 87,6 % housewives were graduated from elementary school. About 50% household heads have a main job as laborers. The average household¡¦s income is Rp 66.297,51/cap/mo and 62,5% respondents are classified under poverty line with spending money for food as about 73,1 % and for non food 26,9%. Energy and protein intake before and after intervention is increased from 60,9% to 71% and 90,5% to 106,.7% , respectively. For rate of Food Security, before intervention all families (100%) are classified as not resistant (SKP < 6), but after intervention there are four families (12.4%) improved to resistant rate (SKP „d 6). However, statistical analysis by t-test showed there is no significant difference, therefore it¡¦s necessary to prolong the intervention. The results of observation about ¡§coping mechanism¡¨ were, about 69,8% households prefered the way of purchasing foods with instalment credit in groceries, some households borrowed money from their neighbors or close families, or by working as tenants, construction laborers and drivers, or change their animals to a needy foods, or goes to a pawn shop.